THE EGGS AND EARLY DEVELOPMENTS OF TWO EELS FROM ViZHINJAM. - George, Rani Mary (Indian Journal of Fisheries, 2011)
The eggs and early developments of an Ophichthyid and a Muraenid eelsof Vizhinjam nearshore waters are recorded. The eggs, which were in theearly stage of development on the day of collection, began to hatch out on thefourth day. Details of the different stages along with observations made by earlierworkers are given